The Effect of Alpinia Purpurata K. Schum Rhizome Extract Supplementation in Tris-Egg Yolk Extender on the Quality of Cryopreserved Bali Bull Sperm - Firlina Laila Putri; Sri Rahayu; Agung Pramana Warih Marhendra (Journal of Experimental Life Science)
This study aimed to analyze the effect of Alpinia purpurata K. Schum rhizome extract (APRE) supplementation into tris-egg yolk extender on the sperm quality of Bali bull after freezing. This study used experimental method with a completely randomized design (CRD), consisting of five treatments, denoted as P0 (semen diluted using 100% Tris-Egg Yolk (TEY)), P1 (semen diluted using 98% TEY and 2% APRE), P2 (semen diluted using 96% TEY extender + 4% APRE), P3 (semen diluted using 94% TEY + 6% APRE), and P4 (semen diluted using 92% TEY + 8% APRE). Semen quality was assessed both before and after freezing, using several indicators such as motility, viability, and abnormality of sperm. The antioxidant activity of RGE was determined using the DPPH (1,1-diphenils-2-picrylhydrazils) technique. The data were analyzed using ANOVA with further analysis using post hoc tests in the SPSS 25 program. The results showed that APRE has strong antioxidant activity, with an IC50 value 38.004 μg.mL-1. Meanwhile, this research has shown that the addition of 6% RGE in the tris-Tris-egg yolk extender was able to maintain sperm quality before and after freezing.